2020
DOI: 10.2147/prom.s238673
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinically Meaningful Difference for the Infant Gastroesophageal Questionnaire Revised version (I-GERQ-R): A Quantitative Synthesis</p>

Abstract: Background: Gastroesophageal reflux disease (GORD) is a common condition affecting 30% of infants aged 0-23 months. The Infant Gastroesophageal Questionnaire Revised version (I-GERQ-R) is an observer-reported outcome measures (ObsRO) developed to evaluate the impact of GORD on young infants. However, evidence regarding the clinically important difference (CID) for the I-GERQ-R is limited. The aim of this study was to determine a CID for the I-GERQ-R. Methods: A literature review was undertaken (PsycInfo, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is not surprising that there is overlap between the results of these questionnaires based on similar symptom questions but this overlap in their diagnostic capabilities might significantly impact research findings and clinical practice. These instruments have been commonly used in pediatrics and the I‐GERQ‐R, in particular, has been utilized in numerous studies as a reflux‐specific outcome and in many ways has informed our understanding of reflux epidemiology and response to treatment in infants and young children (16–19,21–23,26–28). Our results call into question whether the I‐GERQ‐R is truly measuring reflux alone or if it is actually reflecting oropharyngeal dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that there is overlap between the results of these questionnaires based on similar symptom questions but this overlap in their diagnostic capabilities might significantly impact research findings and clinical practice. These instruments have been commonly used in pediatrics and the I‐GERQ‐R, in particular, has been utilized in numerous studies as a reflux‐specific outcome and in many ways has informed our understanding of reflux epidemiology and response to treatment in infants and young children (16–19,21–23,26–28). Our results call into question whether the I‐GERQ‐R is truly measuring reflux alone or if it is actually reflecting oropharyngeal dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…It has historically been used to both diagnose and monitor reflux symptom burden in epidemiologic and pivotal pharmacologic studies (17)(18)(19)(20)(21)(22)(23). With an abnormal cutoff above a score of 16 as signifying clinically significant GERD as validated against caregiver symptom reports, I-GERQ-R continues to be widely utilized for studies of reflux prevalence and clinical trial reporting (16,(24)(25)(26)(27)(28)(29).…”
Section: What Is Newmentioning
confidence: 99%
“…The gastroesophageal reflux disease questionnaire (GerdQ) is a self-report questionnaire that contains two reflux symptom-related positive questions, two gastrointestinal symptom-related negative questions, and two reflux symptom impact-related positive questions. 11 In our previous study, GerdQ demonstrated a high diagnostic value for predicting GERC at a cutoff point of 8.0, with a sensitivity of 66.7% and a specificity of 91.7%, compared with MII-pH. 12 Moreover, the GerdQ impact scale (GIS) has a score range of 0–6 and contains two reflux symptom impact-related positive and negative questions.…”
Section: Introductionmentioning
confidence: 99%